The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/curroncol29120733
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Quality of Life in a Post-Prostatectomy Ablative Radiation Therapy (POPART) Multicentric Trial

Abstract: Background: The aim of this study was to investigate the feasibility of ultrahypofractionated radiotherapy to the prostate bed in patients with biochemical and/or clinical relapse following radical prostatectomy who were enrolled in the prospective, observational, multicentric POPART trial (NCT04831970). Methods: Patients with post-radical prostatectomy PSA levels of ≥0.1–2.0 ng/mL and/or local relapse at PSMA PET/CT or multiparametric MRI were treated with Linac-based SBRT on the prostate bed up to a total do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…up to the level of cut end of vas deferens), unless of course there was initial seminal vesicle invasion [1] . This approach is similar to the recent multicentric, prospective, observational POPART trial, testing extreme hypofractionation in patients with biochemical and/or clinical relapse [30] . Even when a local relapse was visible on PSMA PET/CT or mpMRI (in 26% of patients), the entire prostate bed was (albeit stereotactically) irradiated.…”
Section: Discussionmentioning
confidence: 92%
“…up to the level of cut end of vas deferens), unless of course there was initial seminal vesicle invasion [1] . This approach is similar to the recent multicentric, prospective, observational POPART trial, testing extreme hypofractionation in patients with biochemical and/or clinical relapse [30] . Even when a local relapse was visible on PSMA PET/CT or mpMRI (in 26% of patients), the entire prostate bed was (albeit stereotactically) irradiated.…”
Section: Discussionmentioning
confidence: 92%
“…We recently demonstrated that highly focused radiation in a few fractions to the prostate bed can be safely delivered, with no significant acute ≥ G2 side effects nor deterioration in patient-reported QoL measures [15] . The present findings with an extended follow-up validate these initial data, thus adding further evidence that post-operative SBRT has favourable toxicity profiles in the short to medium term.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility criteria and treatment procedures have been previously reported in detail [15] . Briefly, patients enrolled in the trial should have had a biochemical relapse following RP (any type) with the prostate-specific antigen (PSA) not exceeding 2.0 ng/mL and no distant metastases on [18F]-PSMA positron emission tomography (PET) within 60 days prior to registration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations